Fearless cross-platform development with Delphi : expand your Delphi skills to build a new generation of Windows, web, mobile, and IoT applications /: expand your Delphi skills to build a new generation of Windows, web, mobile, and IoT applications. (2021) - Cornelius, David
No abstract available